Self Management Pasien Pasca Stroke Di Wilayah Kerja Puskesmas Bontomarannu Kab.Gowa - Sulasri Sulasri; Suntin Suntin; Nurhalimah Nurhalimah; Alamsyah Alamsyah (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: Stroke is a disease of the brain consisting of disruption of local or global nerve function, inhibiting sudden, progressive, and fast, which develops (in seconds or minutes) which lasts more than 24 hours to attack modern society and cause physical, mental and also good disability when productive also old age. The main problems faced by stroke patients are family problems, the environment and medical staff to meet the needs of care and assistance because they require continuous care in order to improve the quality of life that can have an increasing effect on the physical good medically and help cure the disease repeatedly. Purpose: The purpose of this study was to determine the relationship between self-management of post-stroke patients. Methods: This type of research is a descriptive analytic with cross sectional. Results: The results of the study obtained from the Chisquare statistical test obtained the value of ? = 0.002 (? <? = 0.05), which means there is a significant relationship with self-management statistics with post-stroke patients. Conclusion: that research on self-management related to patients can be improved post stroke.